Ecdysis‐related neuropeptide expression and metamorphosis in a non‐ecdysozoan bilaterian. (1st September 2021) - Zieger, Elisabeth; Calcino, Andrew D.; Robert, Nicolas S.M.; Baranyi, Christian; Wanninger, Andreas
Abstract: Ecdysis‐related neuropeptides (ERNs), including eclosion hormone, crustacean cardioactive peptide, myoinhibitory peptide, bursicon alpha, and bursicon beta regulate molting in insects and crustaceans. Recent evidence further revealed that ERNs likely play an ancestral role in invertebrate life cycle transitions, but their tempo‐spatial expression patterns have not been investigated outside Arthropoda. Using RNA‐seq and in situ hybridization, we show that ERNs are broadly expressed in the developing nervous system of a mollusk, the polyplacophoran Acanthochitona fascicularis . While some ERN‐expressing neurons persist from larval to juvenile stages, others are only present during settlement and metamorphosis. These transient neurons belong to the "ampullary system, " a polyplacophoran‐specific larval sensory structure. Surprisingly, however, ERN expression is absent from the apical organ, another larval sensory structure that degenerates before settlement is completed in A. fascicularis . Our findings thus support a role of ERNs in A. fascicularis metamorphosis but contradict the common notion that the apical organ‐like structures shared by various aquatic invertebrates (i.e., cnidarians, annelids, mollusks, echinoderms) are of general importance for this process.